1980
DOI: 10.1161/01.str.11.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effect of glucose pretreatment on recovery from diffuse cerebral ischemia in the cat. II. Regional metabolite levels.

Abstract: SUMMARY Glucose was Infused intravenously into cats prior to cerebral ischemia. Brain concentrations of glucose, measured in 7 regions, were elevated 2.5-fold compared to those of non-infused animals. Ischemia of 15 or 30 minutes duration caused a greater accumulation of lactic add in the brain of glucose-infused animals. Post-iscbemic restitution of cerebral ATP, phospbocreatine, and lactate during 90 minutes of reclrculation was severely impaired in the brain of animals pretreated with glucose compared to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
78
3
1

Year Published

1981
1981
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(89 citation statements)
references
References 13 publications
7
78
3
1
Order By: Relevance
“…In the bound ary MCA territory, the observed depression in LCMRgIc was out of proportion to the degree of neuronal cell damage. This finding is in agreement with the data of Paschen et al (1983) and Welsh et al (1980), who reported that the distribution of fo cal energy failure within the cortex was most sig nificant in the boundary zone. It is noteworthy that LCMRglc of the non-MCA territory in all three groups exhibited a significant depression that was not accompanied by proportional histological dam age, suggesting that this may be a purely functional response, i.e., diaschisis.…”
Section: Discussionsupporting
confidence: 93%
“…In the bound ary MCA territory, the observed depression in LCMRgIc was out of proportion to the degree of neuronal cell damage. This finding is in agreement with the data of Paschen et al (1983) and Welsh et al (1980), who reported that the distribution of fo cal energy failure within the cortex was most sig nificant in the boundary zone. It is noteworthy that LCMRglc of the non-MCA territory in all three groups exhibited a significant depression that was not accompanied by proportional histological dam age, suggesting that this may be a purely functional response, i.e., diaschisis.…”
Section: Discussionsupporting
confidence: 93%
“…Areas without reflow retain high levels of NADH for several hours (Welsh et al, 1987). Sec ond, the diminution of NADH fluorescence in the ischemic core was similar to that observed previ ously in models of transient, global ischemia (Welsh et al, 1980(Welsh et al, , 1982a and hypoxia-ischemia in neona tal rats (Welsh et al, 1982b) and following transient MCA occlusion in cats (Paschen et al, 1985). In these previous studies, regions with impaired en ergy metabolism exhibited abnormally diminished NADH fluorescence, suggesting that defective gen eration of NADH may limit the production of high energy phosphates (Welsh et al, 1982a).…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies from our laboratory (Myers, 1977(Myers, , 1979aMyers et al , 1983Myers et al , , 1984 and re cently from others (Welsh et al , 1980;Kalimo et al , 1981;Rehncrona et al , 1981) have demon strated that lactic acid accumulation in brain above a threshold concentration of 17 -20 f,Lmol/g in adult cats or monkeys serves as the basis for brain edema and tissue necrosis. Further, although a decrease in energy charge is a precondition for the generation of high lactic acid concentrations in brain, a de creased energy charge by itself is insufficient to in jure the brain (Myers, 1981).…”
Section: Discussionmentioning
confidence: 75%